How do housing prices affect a city’s innovation capacity? The case of China - Ding, Yemin; Chin, Lee; Li, Fangyan; Deng, Peidong; Cong, Shufeng (Technological and Economic Development of Economy, 2023)
Using panel data from 269 Chinese cities, this study examined the impact of housing prices (HP) on cities’ innovation capacity (IC) in China. Firstly, a fixed effect model was used to analyze the effect of HP on cities’ IC in China, revealing that HP positively impacts cities’ IC. Next, several robustness tests were conducted to verify the finding’s reliability. Thirdly, the analysis empirically tested mediating mechanisms between HP and cities’ IC in China. The results show that, on the one hand, higher HP can improve cities’ IC by attracting talents and stimulating the growth of local fiscal revenue. On the other, increasing HP can inhibit cities’ IC in China by attracting funds into the real estate market and impeding residents’ consumption ability. Finally, the heterogeneous nature of the HP–IC link in China was further explored. This study’s results provide recommendations for the government of China on how to promote cities’ innovation performance. First published online 24 August 2023